Identifikasi Potensi Perikanan Air Tawar Di Desa Perigi Landu Kecamatan Sejangkung Kabupaten Sambas - Windi, Uray; Istiqamah, Nur; Muslimah (Politeknik Negeri Sambas, 2021)
Identifying the potential of a region can act as a catalyst for growth and encourage others to develop fisheries on public waters or expand other sectors that could impact the creation of employment. The goal of this study is to find out how much potential the production of captured fisheries is done by the Perigi Landu of Sejangkung district Sambas regency. The method in this study is a quantitative descriptive study because it covers data and data analysis. There are 25 samples in the study than in the analysis using the location quotient analysis technique (LQ). According to the result of this study, the sector in the Perigi Landu Sejangkung district Sambas regency fisheries sector capture water is generally potentially due to having a quality sector > 1 or getting a 3.05.